Dominant Negative c-Jun Inhibits Platelet-Derived Growth Factor- Directed Migration by Vascular Smooth Muscle Cells - Takeshi Ioroi; Motohiro Yamamori; Keiko Yagi; Midori Hirai; Yumei Zhan; Shokei Kim; Hiroshi Iwao (Elsevier, 2003)
The mitogen≫activated protein (MAP) kinase pathways has been shown to be necessary for mitogen-stimulated proliferation, but its role in cell migration has not been fully understood. In this study, we investigated the possible contribution of signaling pathways through c-Jun in platelet-derived growth factor (PDGF)-BB directed cell migration in rat aortic vascular smooth muscle cells (VSMCs) infected with a recombinant adenovirus containing the dominant-negative c-Jun (Ad-DN-c-Jun). DN-c-Jun protein was expressed dose-dependently in VSMCs infected with Ad-DN-c-Jun. Expression of DN-c-Jun significantly inhibited VSMC migration induced by PDGF-BB. Our results provide the first evidence that signaling pathways through c-Jun participates in cell migration induced by PDGF-BB in addition to other MAP kinase pathways in VSMCs.